(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the content of the principles of integration in teaching chemistry, its scientific and methodological foundations, the advantages of its application in the educational process, and modern approaches. It is explained that ensuring interdisciplinary connections in the teaching of chemistry expands the scientific worldview of students, provides a deep understanding of complex chemical processes, and allows for the implementation of a competency-based approach in practice. The article provides types, forms, and mechanisms for increasing the effectiveness of integration, as well as methodological recommendations for combining chemistry with such disciplines as biology, physics, mathematics, ecology, and technology.